Asian therapeutic knowledge and globalization - Laurent Pordié (Revue d'anthropologie des connaissances)
As medical knowledge crosses cultures and borders, brought into contact by trade, conquest, colonialism or religious proselytism, it is subject to cross-cultural histories, reciprocal borrowings and exchanges in the fields of theory and therapy. The history of Middle Eastern and Asian scholarly traditions provides a good account of the transfer of knowledge and the transformation of the forms of therapeutic knowledge that influence each other. Although the dynamism of the healthcare traditions did not appear until rather late, it has fed numerous publications documenting the reworking of therapeutic knowledge and practices. This thematic dossier contributes to this by focusing on contemporary transnational exchanges and reconstructions at work in Asian medicines, which are now also established in Western health systems. Globalization induces encounters between medicines and with new categories of patients, reconfiguring the traditions of care. Practitioners, caught up in these dynamics of globalisation and therapeutic particularisation, are an integral part of these assemblages which make the global and the networks of socio-material influences more complex. If global logics are embodied in the world of care, they do so in a singular manner each time and always anchored in local and diversified processes.